Kærlighedens dialektiker: Karakteristik af Hans Dencks kritiske spiritualisme - Steenbuch, Johannes Aakjær (Dansk Teologisk Tidsskrift, 2014)
Hans Denck (1500-1527) is known as one of the primary characters in the South German Anabaptist movement. Denck has been characterized as a humanist with a high view of the personal freedom of human beings. Based on an analysis of Dencks concept of the difference, or even opposition, between God and human beings, his idea of yieldedness (gelassenheit), spiritualism and conception of the human will, this article argues that Dencks position should be characterized as critical spiritualism rather than humanism, in so far as the spiritual crisis inflicted on human beings